(untitled) (Journal of Academic Research, 2021)
The aim of this study is to use the spoken section of BNC to identify commonly used collocations of spoken English in the belief that these frequently employed, and therefore useful items should be prioritised for teaching to elementary level learners in the EFL classroom. The Compleat Lexical Tutor was used as a tool to access the BNC spoken section as it provides extensive range of samples of British spoken English. It was found that many casual collocations are frequently used in spoken English; these were compiled into a list. Elementary and beginner course books were then analysed in order to investigate the extent to which collocations are used in the early stages of learning. The study offers some examples of collocations and ideas for presenting and integrating them into the curriculum, before presenting the implications of the findings for learning and teaching.